2019
DOI: 10.3390/jcm8122087
|View full text |Cite
|
Sign up to set email alerts
|

Results from the Adverse Event Sedation Reporting Tool: A Global Anthology of 7952 Records Derived from >160,000 Procedural Sedation Encounters

Abstract: Background: The incidence of sedation-related adverse events, inclusive of both adults and children, administered by multiple specialty providers from different countries and venues, using standardized definitions, has never been reported on an international level. We are reporting the outcome data of the adverse event sedation reporting tool as an important step toward a more complete risk assessment of sedation-related morbidity, mortality, and etiology. The analysis of the AE sedation reporting data include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 48 publications
2
13
0
1
Order By: Relevance
“…Our findings were consistent with a previous study analyzing AEs associated with procedural sedatives [34]. Similar to our current study, Mason et al suggested that all reported sedative-induced cardiovascular and respiratory AEs were moderate to sentinel events; however, most of the neuropsychiatric and gastrointestinal AEs caused by procedural sedatives were minimal to minor events [34]. Considering a number of cardiovascular and respiratory AEs are listed as potentially serious AEs in the prescribing information for commonly used sedatives and often occur unexpectedly [35][36][37][38], close monitoring systems must be in place for prompt and appropriate management of sedative-induced AEs, particularly in patients at an increased risk for developing serious AEs associated with sedative use.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings were consistent with a previous study analyzing AEs associated with procedural sedatives [34]. Similar to our current study, Mason et al suggested that all reported sedative-induced cardiovascular and respiratory AEs were moderate to sentinel events; however, most of the neuropsychiatric and gastrointestinal AEs caused by procedural sedatives were minimal to minor events [34]. Considering a number of cardiovascular and respiratory AEs are listed as potentially serious AEs in the prescribing information for commonly used sedatives and often occur unexpectedly [35][36][37][38], close monitoring systems must be in place for prompt and appropriate management of sedative-induced AEs, particularly in patients at an increased risk for developing serious AEs associated with sedative use.…”
Section: Discussionsupporting
confidence: 93%
“…Among them, respiratory system disorders, as well as heart rate and rhythm disorders, were more likely to be serious (ROR 22.046 (95% CI 19.782-24.569) for respiratory system disorders; ROR 16.724 (95% CI 15.379-18.187) for heart rate and rhythm disorders); in contrast, nervous system disorders were less likely to be serious (ROR 0.519 (95% CI 0.470-0.573)). Our findings were consistent with a previous study analyzing AEs associated with procedural sedatives [34]. Similar to our current study, Mason et al suggested that all reported sedative-induced cardiovascular and respiratory AEs were moderate to sentinel events; however, most of the neuropsychiatric and gastrointestinal AEs caused by procedural sedatives were minimal to minor events [34].…”
Section: Discussionsupporting
confidence: 93%
“…Anesthetics and analgesics used for sedation provide hemodynamic stability by attenuating the autonomic stress response (Gerstein et al 2016 ). However, sedation itself may decrease respiratory drive, cause upper airway obstruction, and thereafter hypoxia during procedures (Mason et al 2019 ; Amornyotin 2013 ). Severe hypoxia prompts airway intervention such as mask ventilation, thus interrupting the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reporting of the adverse events is not yet a common practice, even though detecting adverse events is a key component for improving the quality of care and patient safety during procedural sedation 11 . Only 39% of the respondent reported recording the adverse events in the hospital database, which would allow systematic evaluation better than recording the events only in patient files.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, precautions for patient safety should be properly considered in off‐site administration of procedural sedation 10 . The most common adverse events are airway obstruction, apnoea and oxygen desaturation, while agitation, nausea, laryngospasms and haemodynamic instability occur occasionally 11 . International guidelines emphasise the evaluation of individual patient‐related risks and proper training for administration of sedation and management of adverse events, including handling of age‐ and size‐appropriate equipment for monitoring, securing the airway and ventilating the patient 12,13 …”
Section: Introductionmentioning
confidence: 99%